Improvement of Power Quality with LPF-PI-MSRF Controller in Fuel Cell Integrated Unified Power Quality Conditioner - Addala Satyanarayana (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In modern world, power demand is increasing every day, and with that, power quality complications are also increasing. In order to rectify these power quality problems, we are using custom power devices to reduce these problems. In that custom power device, UPQC is the best device to reduce most of the power-related issues in the electricity market. The growing penetration of fuel cells and other renewable energy sources into the electrical grid calls for efficient ways to handle power quality problems. In order to develop power quality in dispersed generating systems, this paper suggests a novel approach that integrates a fuel cell (FC) with a unified power quality conditioner (UPQC). By reducing voltage sags, swells, harmonics, and other power quality disruptions, these technologies work in concert to create a power supply that is more dependable and resilient. The beneficial effects of fuel cells and UPQC combine in the Fuel Cell-UPQC (FC-UPQC) system. While UPQC is a flexible power-conditioning tool that can handle a variety of power quality problems, fuel cells provide clean and sustainable power generation. By integrating these technologies, a complete solution is achieved, which encourages the effective use of renewable energy sources while also guaranteeing a steady supply of electricity. The architecture of the FC-UPQC system is discussed in the article, along with an overview of its main parts and how they work. In order to maximize the integrated system’s performance and guarantee smooth operation and significant power quality improvement, control solutions are discussed. The efficiency of the suggested FC-UPQC system under various operating situations and power quality disturbances is validated by the simulation results.